Pendekatan Utilitarian Prevention Deterence dalam Meminimalisir Kenakalan Remaja - Bustomi Bustomi; La Ode Risman (Pusat Riset dan Inovasi Nasional, 2025)
Children are a mandate given by the Creator to His creatures who must be guarded, cared for and given the best education so that their physical and spiritual lives are fulfilled. In Law Number 23 of 2002, a child is defined as someone who has not reached the age of 18, while the definition of a child in the juvenile justice procedure law Number 13 of 2013 is 12 to 18 years old. Guidance and supervision of children are very necessary both in the family, community and school environments. The purpose of control is so that children do not get caught up in associations that violate regulations or commit crimes, children must always be guarded and given an understanding of the importance of norms, both norms of politeness, moral norms and religious norms. Children commit crimes or violations, so in terms of the law it is not given a child who is in conflict with the law, of course when a child commits a crime must be treated differently in legal handling, because from a psychological perspective children still have hope in achieving their dreams and future ideals. Children as perpetrators of deviant acts, if the delinquency committed is categorized as minor, then the resolution of the punishment can be through peace or guidance, but if the child commits a serious violation or crime, the implementation of the law will continue but prioritize special treatment that is in accordance with the psychology of children under the age of 18 years. Community Service Activities are carried out by academics from the Faculty of Law in the Law Study Program, Dharma University of Indonesia (UNDHI) in collaboration with the National Child Development Institute (LEMBIKNAS) located at the Darut Tahsin Islamic Boarding School, Citeras District, Lebak Regency-Banten. Based on the theme, there are two formulations of the problem, namely: 1) How is the Utilitarian Prevention Deterrence theory in dealing with naughty children? 2) What are the sanctions for naughty children who commit minor and serious violations from the Utilitarian Prevention Deterrence perspective? The method used is qualitative by analyzing based on theories, books, journals, legal dictionaries and related laws and regulations. Through community service activities, hopefully there will be enlightenment on the resolution when children commit deviant acts.